Design and Development of a Brain Computer Interface Controlled Robotic Arm - Khow, Hong Way (2015)
An electroencephalogram (EEG) signal is a brain signal recorded from human scalp by using electrodes. Brain computer interface (BCI) is a system that allows human to communicate with electronic device by using brain signal. The aim of this project is to design and develop a BCI controlled robotic arm using EEG signal. In this project an EPOC (a headset consists of 14 electrodes) is used to detect and collect EEG signal from human scalp. Every facial expression made by human beings generates a specific EEG signal, the BCI robotic arm is designed to be controlled by human expressions. The robotic arm created in this project is able to make 4 moves (Make a fist, release fist, flexion of elbow and extension of elbow). Each move is controlled by one expression (Left smirk, right smirk, raise brow, and look left/ right). The performance of the BCI robotic arm is determined by testing it on 10 subjects. The average accuracy of the system is above 92%. We have analyzed the effect of decreasing the number of electrodes on the proposed BCI system. It has been concluded that 7 electrodes are ehough to control the robotic arm. The accuracy of the BCI system with reduced number of electrodes (7 only) for 10 subjects is above 90%.